Výroba upevňovací podložky - Dráždil, Jindřich (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Práce se zabývá řešením výroby upevňovací podložky, která je určena do zámku kabelového svazku. Je vyrobena z materiálu 1.4310 o tloušťce 0.7 mm, roční předpokládaná výroba je 12.000 kusů. Jako nejvhodnější způsob výroby byla zvolena technologie sdruženého nástroje ve stroji LEN 24 C, a to na základě zvolené nejvhodnější technologie výroby, výpočtech a technicko-ekonomickém zhodnocení.

The work deals with the solution of the production of a fastening washer, which is intended for the lock of the cable harness. It is made of the 1.4310 material with the thickness of 0.7 mm; the annual production is estimated at 12,000 pieces. The technology of the combined tool in the LEN 24 C machine was chosen as the most suitable method of production, based on the chosen most suitable production technology, calculations and technical and economic evaluation.
Production of mounting pad
Keywords: sdružený nastroj; Len 25 C; upevňovací podložka; plošné tváření; combined press tool; Len 25 C; fastening washer; flat forming